Helical repeat of DNA in solution. The V curve method. - Goulet, I (1987)
The V-like dependence of the electrophoretic mobility of small DNA rings on their topological constraint, which has been documented in a recent paper [Zivanovic et al. (1986), J. Mol. Biol., 192, 645-660], has been explored as a tool to measure the helical twist of the torsionally unstressed duplex. The method was applied to single mixed sequence fragments approximately 350 to 1400 base pairs in length, providing estimates of their average helical periodicity. It was also used to compare two DNA fragments, and to evaluate the helical repeat of poly(dA.dT).poly(dA.dT) and poly(dA).poly(dT) inserts, and the helix unwindings associated with dA and dC methylations by dam and Hhal methylases, respectively. Data were found to be highly reproducible and helical repeat estimates were in good agreement with those obtained from previous techniques.